Exploring Malaysian students’ mathematical thinking skills - Ibrahim, Hasniza; Tunku Ahmad, Tunku Badariah; Isa, Norshahira (INSTITUT AGAMA ISLAM NEGERI PADANGSIDIMPUAN, 2023)
Mathematical thinking is a fundamental aspect of mathematics education and encompasses a range of cognitive processes. It is a crucial part of mathematics for students who desire to continue higher level mathematics. This research aims to investigate the students’ mathematical thinking based on the four elements of mathematical thinking, namely specializing, generalising, conjecturing and convincing. In addition, this study also aims to determine which element of mathematical thinking is the most difficult among students. This study employed a nonexperimental descriptive research design, and fifty (50) Form Four students from a public school in Johor, Malaysia, have been chosen as the sample of this study. A Mathematical Thinking Test (MTT) was used as an instrument in this study to collect the data. The test results showed that students are lacking in mathematical thinking skills, especially the conjecturing element, which was the most difficult element among the students. Therefore, teachers and other relevant authorities should pay closer attention to this issue. This study suggests that it is necessary to find solutions to overcome student difficulties in learning mathematics. Besides, this study established the instrument's validity and reliability in assessing mathematical thinking. Hence, it can be replicable and practical to be used to measure secondary school students' mathematical thinking.